Experiences of Food Insecurity Among Pregnant Adolescents and Adolescent Mothers in Ghana: A Photovoice Method - Isabelle Posey; Christiana Nsiah-Asamoah; Nicholas Fergusson Russell; Esther Darkwa Entwi; Harriet Okronipa (Frontiers Media S.A., 2024)
Objectives: Food insecurity (FI) remains a major public health problem globally. However, there is limited information about adolescents' experiences. The current study explored FI experiences of pregnant adolescents and adolescent mothers in Cape Coast, Ghana using a Photovoice method.Methods: This study recruited 34 pregnant adolescents and adolescent mothers from communities in Cape Coast, Ghana. Each participated in a training session then was provided prompts to take photos that portrayed food access barriers, facilitators and coping strategies. In a debrief session, each participant selected two pictures they took and explained the image, followed by a group discussion of the selected photos. Debrief sessions were audio recorded and transcribed verbatim to develop themes using a theory-driven approach.Results: Most participants reported several or many experiences with FI (64.7%) in the previous month. Participants discussed money, unwanted pregnancy, and unstable work as barriers to obtaining food and working, selling goods, and family support as facilitators to obtaining food. Coping strategies mentioned include providing services to others, borrowing food and goods, meal stretching, pawning personal items and trading.Conclusion: The FI experience of this population is complex; interventions, including trade training or school retention, should be multifaceted.